The New Insight into the Role of Antimicrobial Proteins-Alarmins in the Immunopathogenesis of Psoriasis - A. Batycka-Baran; J. Maj; R. Wolf; J. C. Szepietowski (Journal of Immunology Research)
The pathognesis of psoriasis still remains not fully elucidated. Recent advances favor the idea that interactions between innate and adaptive immune response drive inflammatory process in this disease. Innate antimicrobial peptides and proteins (AMPs) are diverse group of small molecules that provide the first line of defense against invading pathogens. In recent years, the novel functions of AMPs have been identified. There are three subclasses among AMPs that have gained the special interest as a potentially important player in the pathogenesis of psoriasis: cathelicidin, S100 proteins, and defensins. These AMPs have been shown to modulate and trigger host immune response in psoriasis acting as interplayer between innate and adaptive immune mechanisms. Overexpressed in psoriatic lesions, they prime immune cells for enhanced production of proinflammatory mediators and act as chemoattractant for leukocytes. Therefore, the novel term describing AMPs alarmins has been suggested. As multifunctional player in pathogenesis of psoriasis, AMPs may constitute potential target for therapeutic interventions. However, further investigations are required to establish the methods of downregulation of the aberrant proinflammatory functions of AMPs without increasing the risk of infections.